2014
DOI: 10.1016/j.jvs.2013.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular therapy for long-segment atherosclerotic aortoiliac occlusion

Abstract: Through brachial and femoral artery puncture, PTA, stenting, and CDT, endovascular therapy is feasible for complete long-segment infrarenal aortic occlusion, with lower complication rates and favorable midterm patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
1
17
0
3
Order By: Relevance
“…[1,8,9] Currently, a diagnosis of CAIOD is still an absolute indication for surgical treatment in patients with aortoiliac occlusive disease, because the endovascular technique still suffers from limitations that impede adequate treatment of these patients, although there are already some recent studies that have reported promising results. [11,12] On the other hand, as endovascular techniques are being more and more widely adopted for treatment of patients with aortoiliac occlusive disease, open surgery has come to be reserved for patients with more severe forms of occlusive disease, such as CAIOD. García-Fernández et al [13] found that 24% of a sample of patients operated on for aortoiliac occlusive disease had CAIOD.…”
Section: Discussion:-mentioning
confidence: 99%
“…[1,8,9] Currently, a diagnosis of CAIOD is still an absolute indication for surgical treatment in patients with aortoiliac occlusive disease, because the endovascular technique still suffers from limitations that impede adequate treatment of these patients, although there are already some recent studies that have reported promising results. [11,12] On the other hand, as endovascular techniques are being more and more widely adopted for treatment of patients with aortoiliac occlusive disease, open surgery has come to be reserved for patients with more severe forms of occlusive disease, such as CAIOD. García-Fernández et al [13] found that 24% of a sample of patients operated on for aortoiliac occlusive disease had CAIOD.…”
Section: Discussion:-mentioning
confidence: 99%
“…1,8,9 Currently, a diagnosis of CAIO is still an absolute indication for surgical treatment in patients with aortoiliac occlusive disease, because the endovascular technique still suffers from limitations that impede adequate treatment of these patients, although there are already some recent studies that have reported promising results. 11,12 On the other hand, as endovascular techniques are being more and more widely adopted for treatment of patients with aortoiliac occlusive disease, open surgery has come to be reserved for patients with more severe forms of occlusive disease, such as CAIO. García-Fernández et al 13 found that 24% of a sample of patients operated on for aortoiliac occlusive disease had CAIO.…”
Section: Discussionmentioning
confidence: 99%
“…An intensive development of endovascular methods of treatment has resulted in constantly improving re sults of treatment of aortoiliac occlusive disease and increased qualification of patients for transcatheter treatment. The primary patency of such treatment after 4-5 years fluctuates between 77 and 90%, the secondary one after 3-4 years -between 94 and 96% [18][19][20]. Nevertheless, not all cases can be treated with endovascular methods.…”
Section: Discussionmentioning
confidence: 99%